Extreme frequency selectivity by synchronized time-modulated metasurfaces - Theodoros T. Koutserimpas; Francesco Monticone; Constantinos Valagiannopoulos (Scientific Reports)
Abstract Two coupled, time-modulated metasurfaces are governed by Floquet dynamics and exhibit multiharmonic response once they are electromagnetically illuminated. If they get properly synchronized, some of the developed modes may overlap, a feature that changes dramatically the response of the structure with respect to the operating wavelength. This extreme frequency selectivity is theoretically demonstrated for several alternative setups and the reported findings can revolutionize the design of photonic filters, switches or sensors, based on time-varying media.